Silver buttons - Graham, Bob 1942- (Walker Books and Subsidiaries, 2013)
Bob Graham beautifully captures a world vision in one solitary moment. At 9.59 on Thursday morning, Jodie draws a duck. Just as she is about to add one final silver button to the duck's boots, her little brother takes his first step. At this exact same moment, a man buys bread, a soldier leaves home, a baby is being born...Here is a book, a story, a philosophy so simply told and yet - in true and inimitable Bob Graham style - so rich with emotion and meaning. It is in the smallest details that we sense the greatest significance and can see the big picture. From his glorious urban skyscapes to the tender portrayal of a falling feather or the tying of a shoelace or a dog's joy in scratching his back, Bob lets us in on a world view conveyed with humanity, compassion and affection. This is a book that is sure to connect quietly and powerfully with readers of all ages. The idea that we are all alone, and yet all as one in the world, is drawn with huge sensitivity and poetry
Keywords: Conduct of life -- Juvenile fiction; Bilderbuch